Severe tertiary hyperparathyroidism with severe mandibular injury: case report - Afonso, Eurisane Mendes; Henriques, João César Guimarães; Furtado, Lair Mambrini; Rocha, Marcus Alves; Mitri, Fabio Franceschini; Guedes, Cizelene do Carmo Faleiros Veloso (Journal of Oral Diagnosis, 2020)
Objective: The Hyperparathyroidism is a disease characterized by the increased secretion of a Parathyroid hormone (PTH) in the organism, such as generalized osteoporotic pro- cesses and systemic calcifications. In addition to the skeleton in general, the jaws are also affected by the effects of Hyperparathyroidism. The aim of this study is to present a case of a patient with hyperparathyroidism and mandible lesion. Summary Report: Patient L. F, female gender, 32 years old, asymptomatic, chronic renal disease. Suffering from chronic glomerulonephritis for 4 years, she was referred to a university stomatology ambulatory by her nephrologist, due swelling evaluation on the left side of the face. High level of Parathyroid hormone (PTH) associated to mandibular injury incisional biopsy points at hyperparathyroidism diagnosis. If even after the parathyroidectomy been conducted High level of PTH were still present, it is the case tertiary hyperparathyroidism. Conclusion: It is crucial that dental surgeon examine for hyperparathyroidism whenever there are chronic renal patients affected by osteoporotic mandibular changes